Alterations of xylem transport of key metabolic products of assimilatory activity in soybean: do similar alterations occur in roots and nodules? - do Amarante, Luciano; Lima, Juliana Domingues [UNESP]; Sodek, Ladaslav (Springer Nature, 2022)
The dynamics of changes in key metabolites of N metabolism were investigated simultaneously in roots, nodules and xylem sap following treatments that turn on and off symbiotic N2 fixation in the nodules and nitrate assimilation in the roots. Substantial changes in xylem ureides, glutamine and asparagine are known to mark the functioning of these two processes of N assimilation. The objective was to evaluate whether similar changes in these metabolites occur in the source organs, roots and nodules, as well as the timing of these events. The clearest relationship was found for asparagine, the main product of nitrate assimilation in the root exported in the xylem, where in the presence of nitrate, substantial increases took place in both the xylem and root. The markers of N2 fixation, ureides and glutamine, showed a much less expressive change (ureides) or no significant change (glutamine) in the nodules compared to the substantial change recorded in the xylem. The highly contrasting level of asparagine in the nodule in response to N2 fixation activity has potential as a diagnostic tool for activity of this assimilatory process. The timing of changes in the source organs coincided with that of the xylem. Activities of glutamine synthetase, glutamine oxoglutarate amino transferase and asparagine synthetase in roots and nodules varied according to the treatment, consistent with changes in assimilatory activity. A short period of N starvation accelerated nitrate uptake and assimilation in the roots when nitrate became available. The evidence did not support nitrate assimilation in nodules.
Keywords: N metabolism; Nodule; Root; Soybean (Glycine max L.); Xylem sap